Children's cultures: reiteration and the conceptions of time in early childhood education - Susana Angelin Furlan; José Milton de Lima; Márcia Canhoto de Lima (Universidade Federal de Santa Catarina, 2019)
This article depicts a survey in a municipality in São Paulo State, which aimed to deepen the knowledge of one of the four axes of the cultures of childhood: the Reiteration, on the conceptions of children's time of teachers investigated and still, analyse the reactions of children in relation to such positions. Were subject of research two teachers of two Infant classes I, with children of 3 to 4 years of age. The methodology used was based on the qualitative approach, characterized as Ethnography. It appeared, from the bibliography, there are several conceptions of time: Chronos, Kairos and Aión, and Chronos, time of the routines is what reigns inside the school. The children, however, reinvent their time and so create what we call a new understanding of time, the Kaiônico, or the reiteration, marked by the subjective way of understanding of children, playing with the hours of the clock, stopping them and returning them when they want.